Synthesis and biological activity evaluation of 3-(hetero) arylideneindolin-2-ones as potential c-Src inhibitors. (31st December 2022) - Princiotto, Salvatore; Musso, Loana; Manetti, Fabrizio; Marcellini, Valentina; Maga, Giovanni; Crespan, Emmanuele; Perini, Cecilia; Zaffaroni, Nadia; Beretta, Giovanni Luca; Dallavalle, Sabrina
Abstract: Inhibition of c-Src is considered one of the most studied approaches to cancer treatment, with several heterocyclic compounds approved during the last 15 years as chemotherapeutic agents. Starting from the biological evaluation of an in-house collection of small molecules, indolinone was selected as the most promising scaffold. In this work, several functionalised indolinones were synthesised and their inhibitory potency and cytotoxic activity were assayed. The pharmacological profile of the most active compounds, supported by molecular modelling studies, revealed that the presence of an amino group increased the affinity towards the ATP-binding site of c-Src. At the same time, bulkier derivatizations seemed to improve the interactions within the enzymatic pocket. Overall, these data represent an early stage towards the optimisation of new, easy-to-be functionalised indolinones as potential c-Src inhibitors.